1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Variable Separation and Partial Fractions

  1. Sep 7, 2010 #1
    1. The problem statement, all variables and given/known data

    dx/dt=3x(x-5); x(0)=2

    2. Relevant equations

    dx/dt=F(x)G(t)

    dx/dt=x'

    3. The attempt at a solution

    First I separated the variables using F=3x(x-5) and G=3

    x'/(3x(x-5))=3

    Applying method of quadrature:

    [tex]\int\frac{x'}{(3x(x-5)}dt=\int3 dt[/tex]

    On the right hand side I end up with 3t. For the left hand side I get an integral I need apply partial fractions.

    After solving the partial fraction I have:

    [tex]\int\frac{1}{5x-25}-\frac{1}{5x}[/tex]

    Integrating that leaves me with:

    1/5ln|5x-25|-1/5ln|5x|=3t+c

    Multiplying both sides by 5:

    ln|5x-25|-ln|5x|=15t+c

    Applying log property where ln|a|-ln|b|=ln|a/b|

    [tex]ln\frac{5x-25}{5x}[/tex]

    Reducing that by 5:

    [tex]ln\frac{x-5}{x}[/tex]

    So finally I have...after taking e of both sides:

    [tex]\frac{x-5}{x}=e^{15t}+c[/tex]

    I am kind of stuck here solving for c...assuming I've done the above correctly.

    The initial condition shows x(0)=2.

    I've tried sub'ing in x=2 and t=0 to no avail. I've either done something wrong at the top or messed up this last part.

    Any help will be appreciated.
     
  2. jcsd
  3. Sep 7, 2010 #2
    All you need to do is solve for x! Try multiplying both sides of the equation by x, then isolating all 'x-terms' on one side. From there, you it will become clear what other steps need to be taken to determine your solution.
     
  4. Sep 7, 2010 #3

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    You don't need to solve for x. What makes you think you've done anything wrong so far? It looks ok to me. Just put x=2 and t=0 and solve for c. What answer are you expecting to get?
     
  5. Sep 7, 2010 #4
    The answer in the back of the book is:

    [tex]x(t)=\frac{10}{2+3e^{15t}}[/tex]

    Besides the fact that I can't seem to get to that answer, I've tried about six of these using the same method and end up with the same result - a similar answer but not correct.

    If I plug in the values x=2 and t=0 I get this...

    [tex]x(t)=e^{15t}-\frac{5}{2}[/tex]
     
  6. Sep 7, 2010 #5

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    Ok, I see what you are doing wrong. When you exponentiate log((x-5)/x)=15*t+c you get (x-5)/x=e^(15t+c)=C*e^(15t). The c doesn't remain an additive constant. I missed that, sorry. Now find C and solve for x.
     
    Last edited: Sep 7, 2010
  7. Sep 8, 2010 #6
    Ooooh, that is exactly what I was doing wrong in every problem I tried.

    For some reason I'd do e^15t+c which is e^15t*e^c. e^c is still a constant but rather than keep it as a multiplier, I'd throw in as a plus c. Now I see what I was doing wrong.

    Perfect. Thank you!
     
  8. Sep 8, 2010 #7
    Actually, I think I am still missing something.

    Using (x-5)/x=ce^15t and x(0)=2, I come up with x(t)=-3/2e^15t

    Which isn't even close.:confused:
     
  9. Sep 8, 2010 #8

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    How did you manage that? I get (x(t)-5)/x(t)=(-3/2)*e^(15t) to start out with ok, now you still have to solve for x(t).
     
  10. Sep 8, 2010 #9
    Maybe that is my problem. I used x(0)=2 to get x(t)=-3/2e^15t

    (x-5)/x=ce^15t -> (2-5)/2=ce^15(0) which got me x(t)=-3/2e^15t...if that makes sense. To me it seems that is the same thing as solving (x(t)-5)/x(t)=(-3/2)*e^(15t) except I wouldn't have had the -3/2 like you have..since I had to use x(0)=2 to get that.
     
  11. Sep 8, 2010 #10

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    I don't know what's going through your head. Putting t=0 and x=2 as you said gives c=(-3/2). That's fine. That gives you (x(t)-5)/x(t)=(-3/2)*e^(15t). That's NOT the same as x(t)=(-3/2)*e^(15t). !!??? If the solution were x(t)=(-3/2)*e^(15t) then if I put t=0 into that I get x(0)=(-3/2).
     
  12. Sep 8, 2010 #11
    Trust me, I don't know what's going through my head either. My professor skipped these and the section of the book doesn't go over them either so I have zero idea what I am doing. Sorry for the thick-headedness.

    Let me give it another try.
     
  13. Sep 8, 2010 #12
    Ok...I think this is where I am confused on this step.

    I don't see the difference in this problem between (x(t)-5)/x(t) and (x-5)/x when I am solving for x. I feel like I've solved one and I'm just doing it again.

    Wait...for the x(t) I am not solving for an actual value like I was before when I solved for c before. I am trying solve for x(t)=some equation. Right?

    Being this stupid is painful. :rofl:
     
  14. Sep 8, 2010 #13

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    There is no difference between x and x(t). You just don't always write the '(t)' part to save space. You have (x-5)/x=(-3/2)e^(15t). Now just use algebra to solve for x. Try it. That is x(t). Yes. You are to get a form where x(t) is expressed as a function of t.
     
  15. Sep 8, 2010 #14
    Ok, I definitely get it now and see where I was confused. I was doing some of it out of order compared to how I normally do them.

    Thanks again for putting up with me. I really appreciate it. I wouldn't have understood these without the help.
     
  16. Sep 8, 2010 #15
    Just tried it again and success! I have the exact answer that appears in the back of the book.:biggrin::biggrin::biggrin:
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook